A thick positive electrode and its application

By using VGCF and carbon black as composite conductive agents in the positive electrode of lithium-ion batteries, its physical and chemical properties and ratios are regulated, and the problems of long electron and ion transmission paths and low porosity in thick electrodes are solved, and high magnification, low temperature performance and high temperature cycles are improved.

CN115528247BActive Publication Date: 2025-04-01EVE POWER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211194231.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2025-04-01
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

The application of existing thick electrodes in lithium-ion batteries has problems such as electrons, long ion transmission paths, low porosity, and poor electrolyte wetting, resulting in high DCR of the battery cell, poor rateability and poor low temperature performance.

Method used

VGCF and carbon black are used as composite conductive agents. By regulating its physical and chemical properties and ratios, the electron and ion transmission paths are optimized, the porosity is increased, and the wetting property of the electrolyte is improved.

Benefits of technology

The resistance of the positive electrode thick electrode is reduced, the rate performance and low-temperature performance are improved, and the high-temperature cycle is realized, which improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115528247B_ABST
    Figure CN115528247B_ABST
Patent Text Reader

Abstract

The present invention provides a positive thick electrode and an application thereof. The positive thick electrode comprises a current collector and an active material layer arranged on the surface of the current collector. The active material layer comprises a composite conductive agent. The composite conductive agent comprises vapor grown carbon fiber (VGCF) and carbon black. The vapor grown carbon fiber and carbon black satisfy the relationship: 20≤R×(L / D1)+1 / R×(O1 / B2)≤90, wherein R is the mass ratio of the vapor grown carbon fiber and the carbon black, L / D1 is the aspect ratio of the vapor grown carbon fiber, and O1 / B2 is the structural degree of the carbon black. The positive thick electrode of the present invention uses VGCF and carbon black as the composite conductive agent. By regulating the physical and chemical properties and ratio of the two, the performance of the positive thick electrode can be significantly improved and the resistance of the positive thick electrode can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a thick positive electrode and application thereof. Background Art

[0002] Thick electrode technology is used to prepare high energy density batteries. However, in actual production, lithium-ion batteries with thick electrodes are rarely produced because thick electrodes have long electron and ion transmission paths, low porosity, and poor electrolyte wettability, which ultimately leads to high DCR of the battery cell, poor rate capability, and poor low-temperature performance.

[0003] CN112151743A discloses a pore-forming method for thick electrodes, its products and uses, which coats the slurry on a positive electrode current collector with a roughness of Ra ≥ 1 μm, thereby forming an air channel from the surface of the electrode to the surface of the current collector, effectively solving the problems of poor electrolyte wettability of thick electrodes, long lithium ion migration path, and large concentration polarization.

[0004] CN107093701A discloses a thick electrode with excellent electrochemical performance, and its electrode thickness is greater than 300μm. The thick electrode includes a positive thick electrode and a negative thick electrode. The positive thick electrode includes a positive current collector, a positive active material, a positive binder, a porous carbon conductive agent and a fluorocarbon surfactant. The negative thick electrode includes a negative current collector, a negative active material, a negative binder, a porous carbon conductive agent and a thickener. The porous carbon conductive agent has abundant porous channels and can significantly absorb and retain electrolyte, solving the problems of poor electrolyte wettability of thick electrodes and insufficient utilization of active materials.

[0005] The above solution has the problem that increasing the surface roughness of the current collector will lead to stress concentration on the surface of the current collector, and the problem of tape breakage is very likely to occur during the coating process. Summary of the invention

[0006] The object of the present invention is to provide a positive thick electrode and its application. The positive thick electrode of the present invention uses VGCF and carbon black as a composite conductive agent. By regulating the physical and chemical properties and ratio of the two, the performance of the positive thick electrode can be significantly improved and the resistance of the positive thick electrode can be reduced.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a positive thick electrode, the positive thick electrode comprising a current collector and an active material layer disposed on the surface of the current collector, the active material layer comprising a composite conductive agent, the composite conductive agent comprising vapor grown carbon fiber (VGCF) and carbon black, the vapor grown carbon fiber and carbon black satisfying the relationship:

[0009] 20≤R×(L / D1)+1 / R×(O1 / B2)≤90, wherein R is the mass ratio of vapor-grown carbon fiber and carbon black, L is the length of the vapor-grown carbon fiber, D1 is the outer diameter of the vapor-grown carbon fiber, L / D1 is the aspect ratio of the vapor-grown carbon fiber, O1 is the oil absorption value of carbon black, B2 is the specific surface area of ​​carbon black, and O1 / B2 is the structural degree of carbon black.

[0010] The VGCF in the thick positive electrode of the present invention has a large aspect ratio. Even after the positive and negative active materials expand and shrink, the gaps between the active material particles can be bridged by VGCF, and the transmission of electrons and ions will not be interrupted. The liquid absorption and liquid retention of the pole piece are strongly related to the structural degree of the conductive carbon black. When the structural degree is too high, the carbon black is not easy to disperse, which affects the electronic conduction. The present invention adjusts the physical and chemical properties and ratio of the conductive agent in the thick electrode system, optimizes the electron and ion transmission path, increases the porosity, and improves the wettability of the electrolyte, thereby changing the surface chemistry of the thick electrode, reducing the electronic impedance, improving the rate performance and low-temperature performance, and realizing high-temperature cycling at the same time.

[0011] Preferably, the mass ratio R of the vapor-grown carbon fiber to the carbon black is 0.2-0.5, for example, 0.2, 0.25, 0.3, 0.4 or 0.5.

[0012] Preferably, the aspect ratio L / D1 of the vapor-grown carbon fiber is 25 to 150, for example, 25, 30, 50, 100 or 150.

[0013] During the charge and discharge process of lithium-ion batteries, both positive and negative active materials have expansion and contraction problems, among which lithium iron phosphate (LFP) material has an expansion and contraction rate of 6%. After repeated charge and discharge, the active material particles will become loose, the contact will be reduced, the gap will increase, and they may even detach from the electrode, causing the electron transmission channel to be disconnected, becoming inactive active materials that no longer participate in the electrode reaction, causing cycle diving problems and reduced service life. VGCF has a large aspect ratio. Even after the positive and negative active materials expand and contract, the gaps between the active material particles can be bridged by VGCF, and the transmission of electrons and ions will not be interrupted.

[0014] Preferably, the length L of the vapor-grown carbon fiber is 5000-10000 nm, for example, 5000 nm, 6000 nm, 7000 nm, 8000 nm or 10000 nm.

[0015] Preferably, the outer diameter D1 of the vapor-grown carbon fiber is 60-200 nm, for example, 60 nm, 80 nm, 100 nm, 150 nm or 200 nm.

[0016] Preferably, the inner diameter D2 of the vapor-grown carbon fiber is 5 to 30 nm, for example, 5 nm, 8 nm, 10 nm, 20 nm or 30 nm.

[0017] Preferably, the specific surface area B1 of the vapor-grown carbon fiber is 10 to 25 m 2 / g, for example: 10m 2 / g, 12m 2 / g, 15m 2 / g, 20m 2 / g or 25m 2 / g, etc.

[0018] Preferably, the carbon black has a structure degree O1 / B2 of 2.75 to 6.4, for example, 2.75, 3, 4, 5 or 6.4.

[0019] Preferably, the oil absorption value O1 of the carbon black is 220-320 ml / 100g, for example, 220 ml / 100g, 250 ml / 100g, 280 ml / 100g, 300 ml / 100g or 320 ml / 100g.

[0020] Preferably, the specific surface area B2 of the carbon black is 50 to 80 m 2 / g, for example: 50m 2 / g, 55m 2 / g, 60m 2 / g, 70m 2 / g or 80m 2 / g, etc.

[0021] In the thick electrode described in the present invention, the carbon black structure is too high and is not easy to disperse, which affects the electron conduction. When the carbon black structure is too low, two situations will occur: a. The oil absorption value is too small, which will lead to low liquid absorption and liquid retention of the electrode electrolyte, which is not conducive to low temperature performance and long cycle performance; b. The carbon black specific surface area is too large and the secondary particle size is too small, resulting in insufficient contact between the carbon black and the LFP particles. When charged and discharged multiple times, multiple charge and discharge will cause the gap to increase or even some of it to detach from the electrode, resulting in a discontinuous phase of the electron transmission path, becoming a dead active material, and the cycle performance plummets.

[0022] Preferably, the surface density of the positive thick electrode is 250-300 g / m 2 , for example: 250g / m 2 , 260g / m 2 , 270g / m 2 , 280g / m 2 or 300g / m 2 wait.

[0023] Preferably, the active material layer further includes a positive electrode active material and a binder.

[0024] Preferably, the positive electrode active material includes lithium iron phosphate.

[0025] Preferably, the binder comprises polyvinylidene fluoride.

[0026] Preferably, based on the mass of the active material layer being 100%, the mass fraction of the positive electrode active material is 94-97%, for example, 94%, 95%, 96% or 97%.

[0027] Preferably, the mass fraction of the binder is 2-3%, for example, 2%, 2.2%, 2.5%, 2.8% or 3%.

[0028] Preferably, the mass fraction of the composite conductive agent is 1-3%, for example, 1%, 1.5%, 2%, 2.5% or 3%.

[0029] In a second aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the thick positive electrode as described in the first aspect.

[0030] Preferably, the electrolyte injection amount of the lithium-ion battery is 4.5-5.5 g / Ah, for example: 4.5 g / Ah, 4.8 g / Ah, 5 g / Ah, 5.2 g / Ah or 5.5 g / Ah.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The nanocarbon fiber VGCF microstructure of the present invention is hollow, which allows the positive and negative electrodes to absorb more electrolyte, so that lithium ions can be smoothly and quickly embedded, which is conducive to high-rate charging and discharging. VGCF is a high-strength fiber-like material with a large aspect ratio, which can increase the circumventability of the electrode plate. The bonding force between the positive and negative electrode active material particles is stronger, and they will not crack or fall off due to bending. It has high electrical and thermal conductivity. The positive electrode active material has poor electrical conductivity. Adding nanocarbon fibers can improve the electrical conductivity of the positive electrode activity, and also improve the thermal conductivity of the positive and negative electrodes, which is conducive to heat dissipation.

[0033] (2) The present invention changes the surface chemistry of the thick electrode by regulating the physical and chemical properties and ratio of the conductive agent in the thick electrode system, optimizing the electron and ion transmission paths, increasing the porosity, and improving the wettability of the electrolyte, thereby reducing the electronic impedance, improving the rate performance and low-temperature performance, and achieving high-temperature cycling.

[0034] (3) After cold pressing, the volume resistivity of the coating of the positive thick electrode of the present invention can reach below 8.148Ω·cm, the curvature can reach 1, at 0°C, the 90% discharge DCR can reach below 96mΩ, the 60% discharge DCR can reach below 105mΩ, the 30% discharge DCR can reach below 108mΩ, the 25°C 5C discharge gram capacity can reach above 118.2mAh / g, the 25°C 5C discharge percentage can reach above 82.1%, the 0°C 3C discharge gram capacity can reach above 94.3mAh / g, the 0°C 3C discharge percentage can reach above 74.2%, and the 45°C 1C / 1C cycle capacity retention rate can reach above 85.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a comparison chart of the cycle performance of the thick positive electrodes prepared in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0037] The material parameters in the embodiments of the present invention and the comparative examples were tested by the following methods:

[0038] 1) Oil absorption value of conductive carbon black

[0039] The oil absorption value O1 of conductive carbon black was measured using a Brabender absorbptometer C according to "Carbon black - Part 2 - Determination of oil absorption value" GB / T 3780.2-2017.

[0040] 2) Specific surface area of ​​VGCF and conductive carbon black:

[0041] The specific surface areas B1 and B2 were measured using a Micromeritics TriStar 3020 specific surface tester in accordance with the "Determination of Specific Surface Area of ​​Solids by Gas Adsorption BET Method" GB / T 19587-2017.

[0042] Example 1

[0043] This embodiment provides a positive thick electrode, and the composition of the positive thick electrode is as follows:

[0044] The mass ratio of lithium iron phosphate, composite conductive agent (conductive carbon black + VGCF), and PVDF is 94:3:3, the mass ratio of VGCF and carbon black is R=0.2 (1:5), the aspect ratio of VGCF (L / D1)=40, the outer diameter D1 is 200nm, the inner diameter D2 is 15nm, the length L is 8000nm, and the specific surface area B1 is 12m 2 / g, the carbon black structure degree (O1 / B2) is 3.69, the oil absorption value O1 is 240ml / 100g, and the specific surface area B2 is 65m 2 / g, R×(L / D1)+1 / R×(O1 / B2)=26.45, the positive electrode sheet surface density is 260g / m 2 .

[0045] Example 2

[0046] This embodiment provides a positive thick electrode, and the composition of the positive thick electrode is as follows:

[0047] The mass ratio of lithium iron phosphate, composite conductive agent (conductive carbon black + VGCF), and PVDF is 95.5:2:2.5, the mass ratio of VGCF to carbon black is R=0.25 (1:4), the aspect ratio of VGCF (L / D1) is 60, the outer diameter D1 is 100nm, the inner diameter D2 is 12nm, the length L is 6000nm, and the specific surface area B1 is 10m 2 / g, the carbon black structure degree (O1 / B2) is 4.2, the oil absorption value O1 is 270ml / 100g, and the specific surface area B2 is 64m 2 / g, R×(L / D1)+1 / R×(O1 / B2)=31.8, the surface density of the positive electrode sheet is 280g / m 2 .

[0048] Example 3

[0049] This embodiment provides a positive thick electrode, and the composition of the positive thick electrode is as follows:

[0050] The mass ratio of lithium iron phosphate, composite conductive agent (conductive carbon black + VGCF), and PVDF is 97:1:2, the mass ratio of VGCF to carbon black is R=0.5 (1:2), the aspect ratio of VGCF (L / D1)=120, the outer diameter D1 is 75nm, the inner diameter D2 is 14nm, the length L is 9000nm, and the specific surface area B1 is 10m 2 / g, the carbon black structure degree (O1 / B2) is 4, the oil absorption value O1 is 300ml / 100g, and the specific surface area B2 is 75m 2 / g, R×(L / D1)+1 / R×(O1 / B2)=68, the surface density of the positive electrode sheet is 280g / m 2 .

[0051] Example 4

[0052] The only difference between this embodiment and embodiment 1 is that the structure degree of carbon black is 2.5, and other conditions and parameters are exactly the same as those in embodiment 1.

[0053] Example 5

[0054] The only difference between this embodiment and embodiment 1 is that the structure degree of carbon black is 6.5, and other conditions and parameters are exactly the same as those in embodiment 1.

[0055] Comparative Example 1

[0056] This comparative example provides a positive thick electrode, and the composition of the positive thick electrode is as follows:

[0057] The mass ratio of lithium iron phosphate, composite conductive agent (conductive carbon black + VGCF), and PVDF is 94:3.5:2.5, the mass ratio of VGCF to carbon black is R=0.17 (1:6), the aspect ratio (L / D1) of VGCF is 15, the outer diameter D1 is 120nm, the inner diameter D2 is 40nm, the length L is 1800nm, and the specific surface area B1 is 8m 2 / g, the carbon black structure degree (O1 / B2) is 2.5, the oil absorption value O1 is 200ml / 100g, and the specific surface area B2 is 80m 2 / g, R×(L / D1)+1 / R×(O1 / B2)=17.6, the surface density of the positive electrode sheet is 260g / m 2 .

[0058] Comparative Example 2

[0059] This comparative example provides a positive thick electrode, and the composition of the positive thick electrode is as follows:

[0060] The mass ratio of lithium iron phosphate, composite conductive agent (conductive carbon black + VGCF), and PVDF is 97.5:0.5:2, the mass ratio of VGCF and carbon black is R=1 (1:1), the aspect ratio (L / D1) of VGCF is 180, the outer diameter D1 is 80nm, the inner diameter D2 is 40nm, the length L is 14400nm, and the specific surface area B1 is 35m 2 / g, the carbon black structure degree (O1 / B2) is 7.3, the oil absorption value O1 is 330ml / 100g, and the specific surface area B2 is 45m 2 / g, R×(L / D1)+1 / R×(O1 / B2)=187.3, the surface density of the positive electrode sheet is 260g / m 2 .

[0061] Comparative Example 3

[0062] The only difference between this comparative example and Example 1 is that VGCF is not added, and other conditions and parameters are exactly the same as those in Example 1.

[0063] Performance Testing:

[0064] The negative electrode active material, CMC, SBR, and conductive carbon black are mixed in a weight ratio of 95:2:1:2, and deionized water is added as a solvent to mix and stir these materials evenly, and then coated on a copper foil. After drying, cold pressing, die-cutting and other processes, the negative electrode plate is obtained. The positive electrode thick plate described in Examples 1-5 and Comparative Examples 1-3 is used as the positive electrode plate, and the above-mentioned positive electrode plate, diaphragm (Enjie 12μm diaphragm is selected) and negative electrode plate are stacked in order. The diaphragm is located between the positive and negative electrode plates to play a role of isolation, and then the core is obtained by lamination or winding; the core is placed in an outer packaging shell (such as an aluminum shell or a soft bag), and after drying, the electrolyte (Zhonghua Blue Sky ZP507 type is selected) is injected according to the injection amount of this patent, and after vacuum packaging, standing, formation, capacity division and other processes, a secondary battery is obtained.

[0065] The obtained secondary battery was subjected to the following electrical performance tests:

[0066] 1) 0℃ HPPC test

[0067] a. At 25±2℃, charge and discharge the battery at 0.5C / 0.5C for 5 weeks;

[0068] b. Place at 0±2℃ for 24h;

[0069] c. 1.0C constant current discharge for 10s, and then stand for 1min;

[0070] d. Adjust SOC to 0.2C and leave for 1 hour;

[0071] e. 1.0C constant current charging for 10s, and then stand for 1min;

[0072] f. Discharge DCR calculation: After adjusting SOC, leave it for 1h, and the terminal voltage is recorded as VD0. Discharge at 1.0C constant current for 10s.

[0073] The terminal voltage is recorded as VD 10 ; DCR = (VD0-VD 10 ) / I

[0074] g. Test the DCR at 90%, 60%, and 30% SOC respectively.

[0075] 2) 25℃ rate discharge performance

[0076] a. Under 25±2℃, place for 10 minutes and cycle the battery at 0.2C / 0.2C for 5 weeks;

[0077] b. Charge the battery to 3.65V at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and leave it for 10 minutes;

[0078] c. Change the discharge current to 0.1C and 5C (A) and conduct multiple rate continuous discharge test;

[0079] d. Discharge at 0.5C current until the battery voltage reaches 2.5V and stop discharging

[0080] e. Record the discharge capacity of the battery cell, calculate the discharge capacity in grams, discharge percentage, etc.

[0081] 3) 0℃ rate discharge performance

[0082] a. Under 25±2℃, place for 10 minutes and cycle the battery at 0.2C / 0.2C for 5 weeks;

[0083] b. Charge the battery to 3.65V at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and leave it for 10 minutes;

[0084] c. Change the discharge current to 0.1C and 3C(A) and conduct multiple rate continuous discharge test;

[0085] d. Discharge at 0.5C current until the battery voltage reaches 2.5V and stop discharging

[0086] e. Record the discharge capacity of the battery cell, calculate the discharge capacity in grams, discharge percentage, etc. The test results are shown in Table 1-2:

[0087] Table 1

[0088]

[0089]

[0090] Table 2

[0091]

[0092] As can be seen from Table 1-2, it can be obtained from Examples 1-3 that the volume resistivity of the coating of the positive thick electrode of the present invention after cold pressing can reach below 8.148Ω·cm, the curvature can reach 1, 0°C, 90% discharge DCR can reach below 96mΩ, 60% discharge DCR can reach below 105mΩ, 30% discharge DCR can reach below 108mΩ, 25°C 5C discharge gram capacity can reach above 118.2mAh / g, 25°C 5C discharge percentage can reach above 82.1%, 0°C 3C discharge gram capacity can reach above 94.3mAh / g, 0°C 3C discharge percentage can reach above 74.2%, and 45°C 1C / 1C cycle capacity retention rate can reach above 85.5%.

[0093] By comparing Example 1 with Examples 4-5, it can be seen that in the thick positive electrode of the present invention, the structure of carbon black will affect its performance. When the structure of carbon black is controlled at 2.75-6.4, the performance of the thick positive electrode is better. If the structure of carbon black is too high, it is not easy to disperse, which affects electron conduction. When the structure of carbon black is too low, two situations will occur: a. The oil absorption value is too small, which will lead to low liquid absorption and liquid retention of the electrode electrolyte, which is not conducive to low temperature performance and long cycle performance; b. The specific surface area of ​​carbon black is too large and the secondary particle size is too small, resulting in insufficient contact between carbon black and LFP particles. When charged and discharged multiple times, multiple charge and discharge will cause the gap to increase or even some of it to detach from the electrode, resulting in a discontinuous phase in the electron transmission path, becoming a dead active material, and a phenomenon of reduced cycle performance.

[0094] The cycle performance comparison diagram of the thick positive electrode described in Examples 1-3 and Comparative Examples 1-3 of the present application is as follows Figure 1 As shown in Table 1-2 and Figure 1 It can be seen that the VGCF in the thick positive electrode of the present invention has a large aspect ratio. Even after the positive and negative active materials expand and shrink, the gaps between the active material particles can be bridged by VGCF, and the transmission of electrons and ions will not be interrupted. The liquid absorption and liquid retention of the pole piece are strongly related to the structural degree of the conductive carbon black. When the structural degree is too high, the carbon black is not easy to disperse, which affects the electronic conduction. The present invention adjusts the physical and chemical properties and ratio of the conductive agent in the thick electrode system, optimizes the electron and ion transmission path, increases the porosity, and improves the wettability of the electrolyte, thereby changing the surface chemistry of the thick electrode, reducing the electronic impedance, improving the rate performance and low temperature performance, and realizing high temperature cycling at the same time.

[0095] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thick positive electrode, characterized in that: The positive thick electrode comprises a current collector and an active material layer disposed on the surface of the current collector, wherein the active material layer comprises a composite conductive agent, wherein the composite conductive agent comprises vapor-grown carbon fiber and carbon black, and the vapor-grown carbon fiber and carbon black satisfy the relationship: 20≤R×(L / D1)+1 / R×(O1 / B2)≤90, wherein R is the mass ratio of vapor-grown carbon fiber to carbon black, L is the length of vapor-grown carbon fiber, D1 is the outer diameter of vapor-grown carbon fiber, L / D1 is the aspect ratio of vapor-grown carbon fiber, O1 is the oil absorption value of carbon black, B2 is the specific surface area of ​​carbon black, and O1 / B2 is the structural degree of carbon black; The mass ratio R of the vapor-grown carbon fiber to the carbon black is 0.2 to 0.5; The length L of the vapor-grown carbon fiber is 5000 to 10000 nm; The outer diameter D1 of the vapor-grown carbon fiber is 60 to 200 nm; The oil absorption value O1 of the carbon black is 220 to 320 ml / 100 g; The specific surface area B2 of the carbon black is 50 to 80 m 2 / g.

2. The thick positive electrode according to claim 1, characterized in that: The aspect ratio L / D1 of the vapor-grown carbon fiber is 25-150.

3. The thick positive electrode according to claim 1, characterized in that: The inner diameter D2 of the vapor-grown carbon fiber is 5 to 30 nm.

4. The thick positive electrode according to claim 1, characterized in that: The specific surface area B1 of the vapor-grown carbon fiber is 10 to 25 m 2 / g.

5. The thick positive electrode according to claim 1, characterized in that: The surface density of the positive thick electrode is 250-300 g / m 2 .

6. The thick positive electrode according to claim 1, characterized in that: The active material layer further includes a positive electrode active material and a binder.

7. The thick positive electrode according to claim 6, characterized in that: The positive electrode active material includes lithium iron phosphate.

8. The thick positive electrode according to claim 6, characterized in that: The binder includes polyvinylidene fluoride.

9. The thick positive electrode according to claim 6, characterized in that: Taking the mass of the active material layer as 100%, the mass fraction of the positive electrode active material is 94-97%.

10. The thick positive electrode according to claim 6, characterized in that: The mass fraction of the binder is 2-3%.

11. The thick positive electrode according to claim 1, characterized in that: The mass fraction of the composite conductive agent is 1-3%.

12. A lithium ion battery, characterized in that: The lithium-ion battery comprises the thick positive electrode according to any one of claims 1 to 11.

13. The lithium ion battery according to claim 12, characterized in that The electrolyte injection amount of the lithium ion battery is 4.5-5.5 g / Ah.

Citation Information

Patent Citations

  • Preparation method of thick electrode with excellent electrochemical performance and lithium ion battery

    CN107093701A

  • Pore-forming method of thick electrode as well as product and application thereof

    CN112151743A

  • Lithium-ion secondary battery

    CN106252712A

  • Electrolyte and lithium ion battery

    CN109935906A